Religiosity and financial development in Africa: evidence from panel quantile regression - Benard Ohene Kwatia; Godfred Amewu; Mohammed Armah (Cogent Business & Management, 2024)
AbstractAs secularism is increasing and religious diversity is regaining momentum worldwide, it is important to understand how systemic religious differences have influenced financial development in Africa. To this end, this study seeks to investigate the impact of religiosity on financial development in Africa by using freedom of religion to proxy religiosity and domestic credit to the private sector to proxy financial development covered from 2000 to 2020. The results from the panel quantile regression show that religiosity is negatively associated with the use of financial services across the quantile, whereas freedom of association, assembly, and civil society, and security and safety are marginally stronger within the lower, middle, and upper quantiles. The findings underscore that, fundamental human rights exert significant influence on financial development in Africa. Our findings contribute to literature by expanding knowledge on the role of personal freedom on economic activities hence, African governments and policymakers constitutionalize freedom as a fundamental human right, as freedom matters for financial development in Africa.